Everyday conversation in dementia: a review of the literature to inform research and practice. Issue 4 (27th November 2016) - Kindell, Jacqueline; Keady, John; Sage, Karen; Wilkinson, Ray
Abstract: Background: There has been increasing interest in dementia care in recent years, including how practitioners, service providers and society in general can help individuals to live well with the condition. An important aspect to this is provision of advice to ensure conversation partners effectively support the person with dementia in conversation. Aims: To provide a descriptive review of the literature examining everyday conversation in dementia in order to inform practice and research. Methods & Procedures: This review used a method specifically developed for reviewing conversation analytic and related literature. A range of databases were searched using key words and explicitly described inclusion criteria leading to a final corpus of 50 titles. Using this qualitative methodology, each paper was examined and data extracted. The contribution of each of these is described and the implications for practice and research are outlined. Main Contribution: This review examined studies into conversation in Alzheimer's disease, vascular dementia and Lewy body dementia, grouping these into: early influential studies; work drawing on positioning theory; studies using social and linguistic approaches; collaborative storytelling; formulaic language; studies specifically using conversation analysis; and conversation as a target for individualized therapy. In addition, more recent work examining primary progressive aphasia and behavioural variant frontotemporal dementia was explored. Overall, this review indicates that research examining conversation in natural settings provides a rich source of data to explore not just the challenges within conversation for those taking part, but also the skills retained by the person with dementia. An important aspect of this understanding is the notion that these skills relate not only to information exchange but also aspects of social interaction. The role of others in scaffolding the conversation abilities of the person with dementia and the potential of this for developing interventions are discussed. Conclusions & Implications: The review indicates that interventions targeting conversation in dementia are often advocated in the literature but currently such approaches remain to be systematically evaluated. In addition, many of the important insights arising from these studies have yet to inform multidisciplinary dementia care practice.